PENGOLAHAN ARSIP FOTO DI KANTOR ARSIP DAN PERPUSTAKAAN DAERAH KOTA YOGYAKARTA - , NASHRUL HAMID ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This report entitled \"The Arrangement of Record Photograph in Kantor Arsip dan Perpustakaan Daerah Kota Yogyakarta\" is the result of data collection Field Work Practices was held at Kantor Arsip dan Perpustakaan Daerah Kota Yogyakarta. Field Work Practiceâs goals are the goal to find a picture on record photograph and to specifically examine the photograph record processing procedures. The scope of the problem, among others, how the processing of photographs record, the means used, and what are the obstacles encountered when processing the photograph record. The method used in the study, includes through interviews, participation observation, and Library Studies. The interview is aimed to obtain more complete information from sources who are experts in the field of records. In the implementation of the Job Training, direct observation is and participation in the processing of the record photograph at Kantor Arsip dan Perpustakaan Daerah Kota Yogyakarta. With this method the author can make direct observations of the condition of photographs record, obtain valid data and konkert associated with the object as a whole, as well as the extent to which the application of archival science with the reality on the ground. After collecting the data, the author ultimately concludes that the processing of record photograph at Library and Archives at Kantor Arsip dan Perpustakaan Daerah Kota Yogyakarta is not fully in line with right archival science is good and right, because human resources have less knowledge about processing of photogrphs record that are marked with corresponding photo yet with procedures and regulations existing mayor.